(untitled) (ETIKONOMI, 2025)
Research Originality: This research examines the asymmetric impact of Islamic bank financing on employment in Indonesia Research Objectives:. This research aims to test the nolinear impact (gn) of Islamic bank financing on employment in Indonesia Research Methods: This research utilizes secondary data from 2006 to 2022 and employs non-linear ARDL (Auto Regressive Distributive Lag) and Conditional ECM (Error Correction Model) analysis methods Empirical Results: In the short term, increases in Islamic bank financing significantly boost labor force participation (LFPR), while decreases have no significant effects. Long-term analysis shows positive changes continue to enhance LFPR, but negative changes do not impact GDP. The impact of financing on LFPR is symmetrical over time, indicating short-term asymmetries do not persist Implications: This research implies that the Indonesian government can boost the growth of Islamic bank financing to increase employment opportunities for the population both in the short and long term. JEL Classification: E24, G21,C32 How to Cite: Cahyono, E. F., Ngah, W. A. S. W., Law, S. H., Mazlan, N. S., Ahmad, M. N. N., & Mohhamed, A. (2025). Evaluating Asymmetric Impacts of Islamic Bank Financing on Employment in Indonesia. Etikonomi, 24(1), 31 – 52. https://doi.org/10.15408/etk.v24i1.40139.